Simulation with Multi Agent Flood Prediction Based on Rain Intensity Using Particle Swarm Otimization - Wahyu Satria Aji (JURNAL TEKNOLOGI INFORMASI, 2019)
Flood is one of the natural disasters that still often occurs in Indonesia. The lack of an adequate warning system is considered as the cause of the flood disaster. At present the flood detection sensor is only around the river which measures the water level, the lack of flood detection around the road bodies causes flooding caused by the high intensity of rain.Simulation model uses a multi agent that is used to detect the point of flooding based on the high intensity of rain, this simulation uses the Multi Agent approach by utilizing intelligent agents. Each agent is simulated using NetLogo at the time of rain by placing the agent into points that have the potential for flooding.This simulation test by placing several agents who have been inserted intelligence to detect locations that have the potential to flood based on the intensity of rain. Each testing agent will move to find the source of rain with the parameters of each agent that has been determined, then the results will be searched for an average value to measure how large the area has considerable potential.